Pregnancy outcomes after ultrasound-guided high-intensity focused ultrasound (USgHIFU) for conservative treatment of uterine fibroids: experience of a single institution. (10th September 2021) - Rodríguez, J.; Isern, J.; Pons, N.; Carmona, A.; Vallejo, E.; Cassadó, J.; De Marcos, J. A.; Paraira, M.; Giménez, N.; Pessarrodona, A.
Abstract: Objective: To assess the impact of ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation for uterine fibroids on fertility. Material and methods: A retrospective observational study was conducted of 560 reproductive-age women with symptomatic uterine fibroids who underwent USgHIFU therapy at Mútua Terrassa University Hospital, Spain, between February 2008 and February 2018. We analyzed pregnancy outcomes including time to conception, pregnancy approach, gestational age, delivery mode, neonatal outcomes and complications during pregnancy and delivery. Results: After USgHIFU treatment, 71 pregnancies were obtained in 55 patients. Of these, 58 (82%) cases were natural pregnancies and 13 (18%) were in vitro fertilization (IVF) pregnancies. The median time to conception was 12 (range 1–72) months. There were 43 (61%) successful deliveries, including a twin gestation, 22 (31%) spontaneous abortions and 6 (8%) therapeutic abortions. The rate of full-term deliveries was 91% (39/43) and the remaining 9% (4/43) were preterm deliveries. Of the 44 live births, 25 (57%) were born vaginally and 19 (43%) by cesarean section. The complications reported included 3 women with retained placenta (7%), 2 with placenta previa (5%) and 1 with severe preeclampsia (2%). The mean birth weight was 3.1 (range: 1.4–4.3) kg, and except for a baby born with a tetralogy of Fallot, all newborns developed well without complications during postpartum and breastfeeding. Conclusion: Patients undergoing USgHIFU treatment of uterine fibroids can achieve full-term pregnancies with few intrapartum or postpartum complications. More studies are required to compare fertility and perinatal outcomes between patients who underwent or not USgHIFU.